2019
DOI: 10.1002/bmb.21255
|View full text |Cite
|
Sign up to set email alerts
|

Using expert data to inform the use of research methods and representations to enhance biochemistry instruction and textbook design

Abstract: Biochemistry textbooks often provide a disconnected, highly mathematical, and decontextualized treatment of thermodynamic and kinetic principles, which renders topics like protein folding difficult to teach. This is concerning given that graduates entering careers, like the pharmaceutical industry, must be able to apply such knowledge and related research methods to solve biochemistry research problems. Thus, it is essential that instructors have strategies to incorporate research methods and representations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…45 More recently, Jeffery et al urged biochemistry instructors to provide their students with experimental data to support their understanding. 27 Although this study included a small number of student interviews, our findings are consistent with the reports of others and thus independently supported.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…45 More recently, Jeffery et al urged biochemistry instructors to provide their students with experimental data to support their understanding. 27 Although this study included a small number of student interviews, our findings are consistent with the reports of others and thus independently supported.…”
Section: Discussionsupporting
confidence: 89%
“…25 Conversely, Walton showed that out-of-class reading assignments of real experimental results improved data analysis skills. 26 Similarly, a 2019 study showed that biochemistry experts use experimental evidence when explaining topics but biochemistry textbooks lack data to support student understanding 27 Students using one of the textbooks evaluated in this study, Integrating Concepts in Biology (ICB), also improved their competencies in the process of science and quantitative reasoning compared to students using a traditional textbook. 28 Schwartz et al sampled over 8000 students from STEM courses at 55 colleges and universities.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Most of the curricula for students in tertiary education suggest three main means of displaying visual information using molecular models of proteins: (i) retrieving structure files from the Research Collaboratory for Structural Bioinformatics Protein Data Bank (RSCB‐PDB) and visualizing them using PyMol 3–6 or another molecular viewer 7–10 ; (ii) encouraging the haptic perception of protein structures using tactile molecular models in combination with visualization of molecular models 11–16 ; (iii) using virtual reality or augmented reality in 3D 17–19 . The wide scale use of molecular models as a visualization tool for learning about proteins has prompted the development of frameworks for evaluating visual literacy in biochemistry 1,2,20 for teachers and students in tertiary education 21–26 …”
Section: Introductionmentioning
confidence: 99%